EFFECT OF ZEOLITE BEADS (DESICCANT BEADS) ON TOMATO SEED STORABILITY AND SEED QUALITY - Ashwini A (Global Journal of Plant and Soil Sciences, 2025)
High temperature and humidity combine to cause rapid seed deterioration of seeds under ambient conditions of storage, causing poor quality seeds hence poor productivity in Agricultural crop production. An investigation was conducted whether seed drying using desiccants (zeolite beads) and airtight packaging would prevent or ameliorate these consequences of storage. The laboratory experiment was laid out in completely randomized design with three replications and five treatments which include storage of seeds using airtight container, airtight container with silica gel (1:1), airtight container with zeolite beads (1:1), poly pouches and cloth bag as control. The difference in moisture content was statistically significant for all the treatments. Seed dried and stored with zeolite desiccant beads showed lowest moisture (2.1%) after 6 months of storage and slightly changed to 2.3% after 8 months of storage, followed by silica gel (5.2%), cloth bag (9.6%), poly pouch (13.3%) and airtight container (13.5%) after eight months of storage period. The seedling vigour index I varied significantly among the treatments. Seed stored with desiccant silica gel showed the highest vigour index I (1747), followed by zeolite beads (1728) compared to cloth bag (1277) at the end of storage period. Seed dried and stored with desiccants silica gel showed the lowest electrical conductivity (0.289 dSm-1) followed by zeolite beads (0.293 dSm-1), compared to cloth bag (0.421 dSm-1) at 8th month of storage. The results demonstrate the superior ability of desiccants to quickly and safely dry seeds prior to and during storage and the benefits of such drying and storing seeds in air tight container to preventing seed deterioration during seed storage under ambient conditions.